2023
DOI: 10.1136/bjsports-2022-106355
|View full text |Cite
|
Sign up to set email alerts
|

Is daytime napping an effective strategy to improve sport-related cognitive and physical performance and reduce fatigue? A systematic review and meta-analysis of randomised controlled trials

Abstract: ObjectiveTo estimate the association between daytime napping and cognitive and physical sport performance and fatigue after normal sleep and partial sleep deprivation (less sleep duration than necessary).DesignSystematic review and meta-analysis.Data sourcesThe PubMed, Scopus, Web of Science, Cochrane Central, SportDiscus and PsycINFO databases.Eligibility criteria for selecting studiesRandomised controlled trials on the effect of daytime napping on sport performance and fatigue available from inception to 2 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…The present results align with two recent meta‐analyses (Boukhris et al, 2023; Mesas et al, 2023), three systematic reviews (Lastella et al, 2021; Sirohi et al, 2022; Souabni et al, 2021), and one narrative review (Botonis et al, 2021) supporting the use of napping as a strategy to boost athletic performance. Previous studies report numerous factors that are positively associated with napping, such as an improvement in alertness (Brooks & Lack, 2006; Tanabe et al, 2020), a reduction of sleepiness (Souabni et al, 2022; Waterhouse et al, 2007), and subjective fatigue (Brooks & Lack, 2006; Souabni et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present results align with two recent meta‐analyses (Boukhris et al, 2023; Mesas et al, 2023), three systematic reviews (Lastella et al, 2021; Sirohi et al, 2022; Souabni et al, 2021), and one narrative review (Botonis et al, 2021) supporting the use of napping as a strategy to boost athletic performance. Previous studies report numerous factors that are positively associated with napping, such as an improvement in alertness (Brooks & Lack, 2006; Tanabe et al, 2020), a reduction of sleepiness (Souabni et al, 2022; Waterhouse et al, 2007), and subjective fatigue (Brooks & Lack, 2006; Souabni et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the objective of the present study was to assess the impact of a 40‐min nap opportunity on perceived recovery (perceived recovery status scale [PRS]), perceived exertion (rating of perceived exertion [RPE]), maximal voluntary isometric contraction (MVIC), and EMG in response to the 5SRT after 1 night of normal sleep (~8 h). The choice of a 40‐min nap duration in our study is based on the findings of a recent meta‐analysis (Mesas et al, 2023), which suggests that naps lasting between 30 and <60 min have been associated with improved physical performance. We presume that an enhancement in short‐term maximal performance and a reduction in neuromuscular fatigue will be observed following a 40‐min nap compared to the no‐nap condition (CON).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various studies have demonstrated that taking a nap has been proven to enhance cognitive performance, facilitate the processing and storage of information, as well as improve learning outcomes and productivity ( 43 45 ). Napping can also alleviate feelings of fatigue and enhance mood states, thereby ameliorating symptoms of anxiety and depression, particularly in the midst of a demanding day or following inadequate sleep the previous night, invigorate you, diminish tension, and enhance your overall sense of well-being ( 46 ). The act of napping also serves to stimulate creativity and foster innovative thinking within the brain.…”
Section: Basic Concepts Of Nappingmentioning
confidence: 99%
“…In the realm of cognitive performance, particularly those linked with exercise, studies have found that water pipe and cigarette smoking diminish cognitive function when compared to nonsmokers. This is particularly apparent in the areas of attention, speed, and reaction time [ 24 , 25 ]. However, certain scholars have also suggested that nicotine intake can significantly improve cognitive performance [ 26 ].…”
Section: Introductionmentioning
confidence: 99%